Creative genesis: escalating naturalism and beyond - Rolston, Holmes, 1932-2025, author; Mohr Siebeck, publisher (Colorado State University. Libraries, 2014)
Does a plausible worldview need some explanations that exceed the natural? Hard naturalisms insist not, but softer, or more open naturalisms find that natural processes can produce ever more complex results - moving from matter to life to mind - in a superb natural history. This invites a religious naturalism, and challenges it. Repeatedly the critical junctures require analysis pressing beyond merely scientific explanations: whether such narrative history is self-explanatory, whether each stage is sufficient for the next when more emerges out of less, what account to give of the creative genesis found in cybernetic genetics, the rise of caring, surprising serendipity, the opening up of new possibility space. Even scientific rationality depends on non-empirical logic, particularly in mathematics. Thoughtful persons are the most remarkable result arising out of natural history. If there is no supernature, at least nature is super. Further still, the intensity of personal experience suggests the Presence of transcending divine Logos, in, with, and under nature.
Lead article in the inaugural issue of this European-based journal on philosophy, theology, and the sciences.
Keywords: hard naturalism; soft naturalism; natural history; genesis; emergence; origin of life; genetics; cybernetics; caring; serendipity; possibility space; nature; supernature; naturalism; Logos